GAYA BAHASA TEKS PIDATO BAHASA INDONESIA PADA ACARA MUHADHOROH DI PESANTREN AR-RAUDLATUL HASANAH 2 LUMUT - Zainilla .; Mina S yanti Lubis; Hasian Romadon Tanjung (Jurnal Education and Development, 2021)
This study aims to find out how the style of language contained in the Indonesian speech text at the muhadhoroh Islamic Boarding School Ar-raudlatul Hasanah 2 Moss. The approach of the research is descriptive qualitative and Indonesian speech text at the muhadhoroh Islamic Boarding School Ar-raudlatul Hasanah 2 Moss as object of the research. The data was analysis by applying data reduction, data presentation, and taking conclusion. From this there are 5 language style besade on sentence structure which consist of 1) climax language style, 2) anticlimax language style,, 3) paralelism language style, 4) repetition language style,, 5) antithesis language style. Based on the result of data analysis, it can be concluded that there are 60 sentences containing the language style in the Indonesian speech tetx at the muhadhoroh event at the Ar-raudlatul Hasanah 2 Moss boarding school, which consists of 14 sentence climax language style, 12 sentence anticlimax language style, 12 sentence paralleslm language style, 12 sentence repetition language style, 10 sentence antithesis language style. Than of 60 sentence containing the language style in the speech text.